Defining the Clinically Meaningful Outcomes for Arthroscopic Treatment of Femoroacetabular Impingement Syndrome at Minimum 5-Year Follow-up. Issue 4 (March 2020) - Nwachukwu, Benedict U.; Beck, Edward C.; Kunze, Kyle N.; Chahla, Jorge; Rasio, Jonathan; Nho, Shane J.
Background: Minimal clinically important difference (MCID), substantial clinical benefit (SCB), and patient acceptable symptomatic state (PASS) have gained prominence as important variables in the orthopaedic outcomes literature. In hip preservation surgery, much attention has been given to defining early clinically meaningful outcome; however, it is unknown what represents meaningful patient-reported outcome improvement in the medium to long term. Purpose: (1) To define MCID, PASS, and SCB at a minimum 5 years after hip arthroscopy for femoroacetabular impingement syndrome (FAIS) and (2) to evaluate the time-dependent nature of MCID, PASS, and SCB. Study Design: Case series; Level of evidence, 4. Methods: Patients undergoing primary hip arthroscopy for FAIS between January 2012 and March 2014 were included. Clinical and demographic data were collected in an institutional hip preservation registry. MCID, PASS, and SCB were calculated for each outcome score including the Hip Outcome Score–Activities of Daily Living subscale (HOS-ADL), Hip Outcome Score–Sport-Specific subscale (HOS-SS), modified Harris Hip Score (mHHS), and International Hip Outcome Tool (iHOT-12) at 1, 2, and 5 years. MCID was calculated by use of a distribution-based method, whereas PASS and SCB were calculated by use of an anchor method. Results: The study included 283 patients with a mean ± SD age of 34.2 ± 11.9 years. The mean changes in 1-year, 2-year, and 5-year scores, respectively, required to achieve MCID were as follows: HOS-ADL (8.8, 9.7, 10.2); HOS-SS (13.9, 14.3, 15.2); mHHS (6.9, 9.2, 11.4); and iHOT-12 (15.1, 13.9, 15.1). The threshold scores for achieving PASS were as follows: HOS-ADL (89.7, 88.2, 99.2); HOS-SS (72.2, 76.4, 80.9); mHHS (84.8, 83.3, 83.6); and iHOT-12 (69.1, 72.2, 74.3). Last, the threshold scores for achieving SCB scores were as follows: HOS-ADL (89.7, 91.9, 94.6); HOS-SS (78.1, 77.9, 85.8); mHHS (86.9, 85.8, 94.4); and iHOT-12 (72.6, 76.8, 87.5). More patients achieved MCID, SCB, and PASS at 2-year compared with 1-year follow-up; however, by 5 years, fewer patients had achieved clinically meaningful outcome (minimum 1-, 2-, and 5-year follow-up, respectively: MCID, 82.6%, 87.3%, 79.3%; PASS, 67.6%, 74.9%, 67.5%; SCB, 62.3%, 67.2%, 56.6%). Conclusion: The greatest proportion of patients achieved MCID, PASS, and SCB at 2-year follow-up after arthroscopic treatment of FAIS compared with 1- and 5-year time points. Improvements were maintained out to 5-year follow-up, although the proportion of patients achieving clinical significance was slightly decreased.